(untitled) (Journal of Hama University, 2021)
The study was conducted on 147 birds and distributed into seven groups, each group consisted of 21 birds. For the first, second, third and fourth groups, a black seed(Nigella Sativa) was added at a ratio of (1, 0.75, 0.5, 0.25)%, respectively, while an anti-coccidiosis (salinomycin) was added to the fifth group at the rate of 0.05% in order to compare its effect with the black seed. As for the sixth and seventh groups, they remained without adding a black seed or an anti-coccidiosis. At the age of 15 days, the first six groups of birds were given the challenge dose (2.6 x104) sporulated oocysts / bird orally of E.tenella. The results of the experiment showed that adding the black seed by 0.5% to the diets of infected bridler chickens led to a significant increase in the average of bird weight and the feed conversion ratio, and the percentage of safety was (67%)and the index of effectiveness of Anticoccidial was moderate compared to rest of the experimental groups, while the indicator of oocysts excretion was 20 in the groups with a black seed added at rates of (0.75, 0.25%) as well as in the fifth group with an anti-coccidiosis, and the percentage of mortality was 9% in the groups of an added black seed at the rate of (0.75, 0.5. 0.25)%.